Jins Shamsudin dies at age 81 - The, Star (The Star, 2017)
PETALING JAYA: Legendary actor Tan Sri Jins Shamsudin has died at the age of 81. The national art laureate was having a meal at his home in Taman Melawati yesterday when he experienced breathing difficulty and was rushed to a clinic nearby where he died at 5.45pm.